Differences in the Effectiveness of Giving Carrot and Red Ginger Juice Against Menstrual Pain in Adolescents - Eva Dwi Ramayanti; Arif Nurma Etika; Indah Jayani (Global Health Science Group, 2020)
Dysmenorrhoea is menstrual pain which is characterized by lower abdominal pain that occurs before menstruation and during menstruation. Dysmenorrhoea if not treated immediately will affect the mental and physical function of the individual, so it must be treated immediately with pharmacological or non-pharmacological therapy. Non-pharmacological therapy, namely herbal treatments such as carrot juice and red ginger cooking water. Carrots contain beta carotene and vitamin E which can reduce the increased production of prostaglandin hormones. Meanwhile, red ginger contains the chemical gingerol which can block prostaglandins so that it can reduce menstrual pain. The purpose of this study was to determine the difference in the effectiveness of giving carrot juice and red ginger to menstrual pain (dysmenorrhea) in adolescents. Pre-experimental research design of two groups pre test-post test. Data collection tool with pain scale questionnaire. Data analysis was performed univariate with frequency distribution and bivariate with Wilcoxon test with computerized assistance. The sample in this study were 36 respondents who were taken using purposive sampling. The group giving red ginger boiled water was more effective in dealing with menstrual pain in adolescents than giving carrot juice.